2017
DOI: 10.1074/jbc.m117.799114
|View full text |Cite
|
Sign up to set email alerts
|

The Tiam1 guanine nucleotide exchange factor is auto-inhibited by its pleckstrin homology coiled-coil extension domain

Abstract: T-cell lymphoma invasion and metastasis 1 (Tiam1) is a Dbl-family guanine nucleotide exchange factor (GEF) that specifically activates the Rho-family GTPase Rac1 in response to upstream signals, thereby regulating cellular processes including cell adhesion and migration. Tiam1 contains multiple domains, including an N-terminal pleckstrin homology coiled-coiled extension (PH-CC-Ex) and catalytic Dbl homology and C-terminal pleckstrin homology (DH-PH) domain. Previous studies indicate that larger fragments of Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 78 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…Structurally, Tiam-1 is composed of a myristoylation sequence, coiled-coil region, PEST, N-terminal and C-terminal PH, extended, Ras binding, PSD-95/DlgA/ZO-1, and DH domains. Similar to other GEFs, Tiam1 is auto-inhibited by its N-terminal PH domain coiled-coiled extension, blocking its GEF activity (Xu Z. et al, 2017). Tiam1 is regulated through phosphorylation, which localizes Tiam1 to the membrane to interact with cell surface receptors (Boissier, 2013).…”
Section: Targeting Tiam1mentioning
confidence: 99%
“…Structurally, Tiam-1 is composed of a myristoylation sequence, coiled-coil region, PEST, N-terminal and C-terminal PH, extended, Ras binding, PSD-95/DlgA/ZO-1, and DH domains. Similar to other GEFs, Tiam1 is auto-inhibited by its N-terminal PH domain coiled-coiled extension, blocking its GEF activity (Xu Z. et al, 2017). Tiam1 is regulated through phosphorylation, which localizes Tiam1 to the membrane to interact with cell surface receptors (Boissier, 2013).…”
Section: Targeting Tiam1mentioning
confidence: 99%
“…Thus, they are poised to mediate cell-autonomous and -nonautonomous functions of Par3 in PCP signaling. It has been reported that the GEF activity of Tiam1 and Trio is autoinhibited through intramolecular interactions (36,37). As a scaffold protein, Par3 may mediate membrane translocation and release of autoinhibition of Tiam1 and Trio to activate Rac signaling in both hair cells and supporting cells.…”
Section: Discussionmentioning
confidence: 99%
“…GEF activities of the full-length proteins can be influenced by auto-inhibitory domains 33 , protein-protein interactions and by phosphorylation of specific residues 34 . Although FL GEF studies may appear physiologically the most relevant, the use of isolated GEF domains limits complexity.…”
Section: Discussionmentioning
confidence: 99%